Occurrence of metastatic eccrine porocarcinoma in an immunosuppressed patient - Mitul B. Modi; Ata S. Moshiri; Toru Shoji; Martin C. Mihm; Xiaowei Xu; David E. Elder (BMC, 2020)
Abstract Background Eccrine porocarcinoma is a rare malignancy accounting for 0.005 to 0.01% of all cutaneous tumors. However, its etiology is not well established. Herein we are reporting the occurrence of metastatic porocarcinoma of the back in a patient with a history of multiple cutaneous malignancies and chronic immunosuppression. Case presentation A 79-year-old male with a history of long-term immunosuppressive therapy for left lung transplantation and multiple cutaneous malignancies including melanoma, presented with an enlargening plaque on the right upper back. Biopsy demonstrated an infiltrative epithelial tumor with aggressive histology and ductal formation. Immunohistochemical stains for p63, CK-5/6, and CEA were diffusely positive, while CK-7 and CK-20 were negative. A diagnosis of eccrine porocarcinoma was made. He underwent complete wide excision with negative margins of the right upper back in January 2018. In November 2018, he was found to have a right posterior shoulder mass, positive right axillary lymph nodes, superficial right upper back soft tissue masses and lymphangitic carcinomatosis involving the left lung. He was transitioned to comfort care and subsequently passed from metastatic disease in December 2018. Conclusion The occurrence of eccrine porocarcinoma in a patient on long term immunosuppressive therapy for lung transplantation suggests a possible role for chronic immunosuppression in the induction of a subset of eccrine porocarcinomas, as in other cutaneous malignancies.